Midnight run [videorecording (DVD)] - Brest, Martin, 1951-; Brest, Martin, 1951-; De Niro, Robert; Grodin, Charles; Kotto, Yaphet, 1939-2021-; Ashton, John, 1948-; Farina, Dennis, 1944-2013 (Universal, 2003)
A bounty hunter is charged with delivering an embezzling, bail-jumping accountant to Los Angeles. What he doesn't know is that the Mob is also after said accountant for embezzling the money in the first place.